Making Sense of Montessori Teacher Identity, Montessori Pedagogy, and Educational Policies in Public Schools - Gerker, Heather E. (Journal of Montessori Research, 2023)
Montessori teachers in public schools navigate a system daily that often does not align with their pedagogy, and district policies push them to stray from high-fidelity implementation. Using Weick’s sensemaking theory and literature on Montessori teacher identity, I contend that Montessori teachers’ identity plays a crucial role in how, or if, they respond to educational policies that may not seemingly align with the Montessori Method. The overarching purpose of this study was to understand Montessori public school teachers’ experiences with policies that influence their pedagogy. Through qualitative interviews and a culminating group-level assessment session, three themes emerged as teachers shared their experiences with educational policies: (a) Montessori pedagogy is more than the materials, (b) districts often force district-wide requirements that are at odds with the Montessori pedagogy, and (c) Montessori teachers in public schools do not feel supported. This article concludes with a discussion of how to better support Montessori teachers in public school settings based on the study’s findings.